Maternal guilt in the lives of female ICU nurses in South Kalimantan, Indonesia: A qualitative study - Yulia Hairina; Nurul Hartini; Nursalam (Belitung Nursing Journal, 2026)
Background: Maternal guilt is a common emotional experience among working mothers, often associated with challenges in fulfilling both professional and caregiving roles. Female nurses, especially those working in intensive care units (ICUs), encounter pressures due to heavy workloads, irregular schedules, and the emotional intensity of patient care. These conditions make them particularly vulnerable to feelings of guilt when family responsibilities are perceived as being neglected. Objective: This study aimed to explore how maternal guilt is experienced in the personal and professional lives of female ICU nurses in South Kalimantan, Indonesia. Methods: A qualitative descriptive design using thematic analysis within a constructivist paradigm was employed. Ten married female ICU nurses who were mothers and had at least five years of ICU experience were purposively recruited through nurse managers from three regional public hospitals. Data were collected through in-depth semi-structured interviews, with member checking and researcher triangulation used to enhance credibility. Interviews were conducted between March and June 2024, transcribed, translated, and analyzed following Braun and Clarke’s six-phase framework. Results: Three themes were identified: (1) the internal burden of perceived inadequacy, reflected in persistent feelings of inadequacy, emotional exhaustion, cognitive overload, anxiety and sadness, and self-blame; (2) relational strain and compensatory parenting, including disrupted parent–child bonding, compensatory parenting behaviors, and increased emotional dependence on spouses; and (3) professional strain and competing care responsibilities, characterized by reduced work focus and distraction, fatigue and thoughts of resignation, and role conflict between professional and maternal responsibilities. These findings indicate that maternal guilt emerged as a multidimensional experience permeating both personal and professional domains. Conclusion: Maternal guilt emerged as a salient experience shaping nurse mothers’ emotional well-being, family relationships, and professional functioning. The findings suggest that collectivist cultural expectations and idealized motherhood norms may contribute to shaping the experience of guilt among Indonesian ICU nurses.  These insights underscore the need for supportive workplace policies, flexible scheduling, and accessible psychosocial services to sustain nurses’ well-being and retention in high-demand clinical environments.